Zagovori - magične korenine medicine - Zupanič Slavec, Zvonka (Etnolog. Nova vrsta (Ljubljana), 2000)
Incantations are the most archaic element in the treasury of folk medical knowledge and no other element is vanishing so fast. Some decades ago incantations were used in folk medicine by only 15% of the Slovenes, while the other practises of folk medicine were based on traditional and empirical knowledge about the curative effects of active substances of plant and animal origin. Nowadays the relation between the magical and religious approach to treating diseases on the one hand, and the scientific approach on the other hand, is probably identical, but what has changed is that the magical and religious component has been replaced by alternative medicine.
Keywords: ethnology; etnologija; ljudska medicina; verovanje; zagovori